(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
This contribution aims to examine the relationship between climate litigation and the principle of separation of powers, questioning about the partial, total, or absent alignment between those who decide and those who ought to decide on climate matters. To address this issue, the analysis will focus on the landmark Klimaseniorinnen judgment delivered by the European Court of Human Rights (ECtHR) in April 2024. This ruling offers valuable insights into the dynamics of the separation of powers principle in this specific field and can also serve as a lens to analyze two climate disputes adjudicated by “domestic courts”: the Italian Giudizio Universale and the French Affaire du Siècle.